Histologic and Genomic Analysis of Conjunctival SCC in African and American Cohorts Reveal UV Light and HPV Signatures and High Tumor Mutation Burden - Gleber-Netto, Frederico O.; Nagarajan, Priyadharsini; Sagiv, Oded; Pickering, Curtis R.; Gross, Neil; Ning, Jing; Yeshi, Melisachew M.; Mitku, Yonas; Tetzlaff, Michael T.; Esmaeli, Bita (Investigative ophthalmology & visual science, 2024)
Conjunctival squamous cell carcinoma (conjSCC) is more prevalent and aggressive in sub-Saharan African countries compared with the rest of the world. This study aims to compare the genomic, immunophenotypic, and histologic features between patients from the United States and Ethiopia, to identify etiopathogenic mechanisms and unveil potential treatment strategies. We compared histologic features and mutational profiles using whole exome sequencing, high-risk human papillomavirus (HPV) status, PD-L1 expression, and tumor-infiltrating lymphocytes in conjSCC tumors of patients from Ethiopia (ETH; n = 25) and the United States (from MD Anderson [the MDA cohort]; n = 29). Genomic alterations were compared with SCCs from other anatomic sites using data from The Cancer Genome Atlas. Solar elastosis was seen in 78% of ETH and 10% of MDA samples. Thicker tumors had higher density of CD8+ and CD3+ cells. HPV status was similar between the cohorts (ETH = 21% and MDA = 28%). The mean tumor mutation burden (TMB) was significantly higher in conjSCC (3.01/Mb, log10) and cutaneous SCC compared other SCC subtypes. ETH samples had higher TMB compared to the MDA cohort (3.34 vs. 2.73). Mutations in genes associated with ultraviolet light (UV) signature were most frequently encountered (SBS7b = 74% and SBS7a = 72%), with higher prevalence in the ETH cohort, whereas SBS2 and SBS13 signatures were more common among MDA HPV+ conjSCCs. Our findings suggest that UV exposure may play a major role in conjSCC, with a higher prevalence in the ETH cohort compared with the MDA cohort, where HPV also contributes.